Water Quality and The Heavy Metal Occurence of Fish in Polluted Watershed - Rizky Muliani Dwi Ujianti; Sutrisno Anggoro; Azis Nur Bambang; Frida Purwanti (Indonesian Association of Food Technologists, 2018)
The clean river is very important for human life and river’s biota. However, many rivers are polluted from both domestic and industrial waste today. Domestic waste comes from households and industrial wastes from nearby industrial activities. One of the biotas of the river is the fish. The objective of the research was to evaluate pollutant and pollutant index in the watershed and the present of Pb in fish in the watershed. The location of this research was a long Garang watershed Semarang, namely from upstream to downstream of the river. The sampling area was divided into 7 segments based on Central Java Governor Regulation No. 156/2010 based on water designation. The studied parameters in this research were heavy metal in fish and water quality. The studied fish was Nila fish (Oreochromis sp.). Results show that Cu was the main pollutant in water river class 1, 2, 3 and 4. DO exceed the limit parameter in water river class 3 and 4. Finally, the highest heavy metals found in fish were found in Pb, while the water pollution index was due to exceeding Cu, all of which came from industrial waste.